Posttranslational Chemical Mutagenesis Methods to Insert Posttranslational Modifications into Recombinant Proteins - Omer Harel; Muhammad Jbara (Molecules, 2022)
Posttranslational modifications (PTMs) dramatically expand the functional diversity of the proteome. The precise addition and removal of PTMs appears to modulate protein structure and function and control key regulatory processes in living systems. Deciphering how particular PTMs affect protein activity is a current frontier in biology and medicine. The large number of PTMs which can appear in several distinct positions, states, and combinations makes preparing such complex analogs using conventional biological and chemical tools challenging. Strategies to access homogeneous and precisely modified proteins with desired PTMs at selected sites and in feasible quantities are critical to interpreting their molecular code. Here, we summarize recent advances in posttranslational chemical mutagenesis and late-stage functionalization chemistry to transfer novel PTM mimicry into recombinant proteins with emphasis on novel transformations.